White Earth Ojibwa and wigwam. / Photographed by Hoard & Tenney, Winona Minnesota - Hoard & Tenney, photographer. (William L. Clements Library, 1870)
Group portrait of five unidentified Ojibwa Indian men wearing mixtures of western and traditional clothing posing outside birch bark wigwam at White Earth Indian Reservation.; No. 305.; Title devised by cataloger.; "Ojibwa Indians" variant names: Anishinaabe, Chippewa Indians, Ojibwe Indians.